Abnormal texture evolution of rolled Mg–3Al–1Zn alloy containing initial 10-12 twins. (1st April 2015) - Lee, Jeong Hun; Park, Sung Hyuk; Hong, Seong-Gu; Won, Jong Woo; Lee, Chong Soo
Abstract : The importance of initial 10-12 twins in the formation of deformation texture was investigated by conducting strain path change tests of rolled Mg–3Al–1Zn alloy in which 10-12 twinning dominated the deformation. The existence of initial twins changed a twinning process by preferring the growth of initial twins rather than the nucleation of new twins, which led to a non-Schmid behavior of twinning characteristics and consequently caused a completely different deformation texture compared with the counterpart without initial twins.